Changes in blood pressure and related risk factors among nurses working in a negative pressure isolation ward - Wang, Yaoyao; Tian, Junzhang; Qu, Hongying; Yu, Lingna; Zhang, Xiaoqin; Huang, Lishan; Zhou, Jianqun; Lian, Wanmin; Wang, Ruoting; Wang, Lijun; Li, Guowei; Tang, Li (Frontiers in Public Health, 2022)
Objective: To observe changes in blood pressure (ΔBP) and explore potential risk factors for high ΔBP among nurses working in negative pressure isolation ward (NPIW). Methods: Data from the single-center prospective observational study were used. Based on a routine practice plan, female nurses working in NPIW were scheduled to work for 4 days/week in different shifts, with each day working continuously for either 5 or 6 hours. BP was measured when they entered and left NPIW. Multivariable logistic regression was used to assess potential risk factors in relation to ΔBP ≥ 5mm Hg. Results: A total of 84 nurses were included for analysis. The ΔBP was found to fluctuate in different working days; no significant difference in ΔBP was observed between the schedules of 5 and 6 hours/day. The standardized score from self-rating anxiety scale was significantly associated with increased risk of ΔBP ≥ 5mm Hg (OR = 1.12, 95% CI: 1.00 - 1.24). Working 6 hours/day (vs 5 hours/day) in NPIW was non-significantly related with decreased risk of ΔBP (OR = 0.70), while ≥ two consecutive working days (vs one working day) was non-significantly associated with increased risk of ΔBP (OR = 1.50). Conclusion: This study revealed no significant trend for ΔBP by working days or working time. Anxiety was found to be significantly associated with increased ΔBP, while no less than two consecutive working days was non-significantly related with ΔBP. These findings may provide some preliminary evidence for BP control in nurses who are working in NPIW for COVID-19.